Implementasi Kebijakan Program Keluarga Harapan (PKH) di Kecamatan Banggai Kabupaten Banggai Laut - Ermawati Lalu; Arifin Tahir; Irawaty Igirisa (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study discusses the implementation of the Family Hope Program (PKH) policy in Banggai District, Banggai Laut Regency, which is one of the government's conditional social protection programs to reduce poverty and improve the quality of human resources through access to education, health, and social welfare. PKH provides cash assistance to very poor families who meet certain criteria, including pregnant women, toddlers, school children, people with severe disabilities, and the elderly. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, involving informants from the Social Service, PKH facilitators, village officials, and beneficiary families. The results show “that, in general,” the implementation of PKH in Banggai District is in accordance with Permensos No. 1 of 2018, which includes planning, determining prospective participants, data validation, distribution of non-cash assistance, assistance through family capacity building meetings (P2K2), commitment verification, data updating, and participant transformation. However, obstacles remain, such as the lack of involvement of non-recipient communities in outreach, misuse of aid for inappropriate purposes, limited communication, and weak coordination between stakeholders. The program's positive impacts are seen in increased access to education for children from poor families, improved health services, and reduced household economic burdens. Although the program's success still depends on strengthening the role of facilitators, increasing supervision, and raising awareness among recipient families to utilize aid appropriately. Thus, the implementation of PKH in Banggai District has contributed significantly to poverty alleviation, but still requires strategic improvements to be more effective and sustainable.